Pond Apple—A Tree Species Adapted to Salt Stress - Guodong| Liu; Yuncong Li; Kimberly Moore; Kim Gabel (EDIS)
This document provides an overview of the Pond Apple (Annona glabra L.), a semi-deciduous tree native to Florida and Puerto Rico. It highlights the tree’s tolerance to salt and flooding, making it suitable for high-salinity coastal landscapes. The Pond Apple can grow up to 10 feet and produces edible fruit similar to custard apples. Ecologically, it is important as its fruit is consumed by wildlife, and its seeds are dispersed by animals. The tree has various uses, including its edible fruit and medicinal properties, with potential anticancer chemicals. Compared to the bald cypress, it is more salt-tolerant but may suffer from iron deficiency in dry conditions.